Methoden der Tanzwissenschaft: Modellanalysen zu Pina Bauschs »Le Sacre du Printemps/Das Frühlingsopfer« - Klein, Gabriele; Brandstetter, Gabriele (transcript, 2015)
In this volume, »Le Sacre du Printemps« by Pina Bausch serves as a shared object of analysis, bundling central methodological approaches to research in the science of movement and dance. This interdisciplinary volume, now appearing in a revised and extended edition, introduces perspectives of Pina Bausch's choreography of the century from the perspectives of cultural studies, social sciences, and the humanities, thus serving as a methodical »toolbox« of research in the science of dance in the germanophone and Anglo-Saxon world. With contributions by Peter M. Boenisch, Gabriele Brandstetter, Stephan Brinkmann, Michael Diers, Mark Franko, Stephanie Jordan, Gabriele Klein, Dieter Mersch, Gerald Siegmund, Hans-Georg Soeffner, Jürgen Raab, and Christina Thurner.